PROCESSING OF WATERMELON RIND DEHYDRATED CANDY - Nur Farah Hani Muhamad; Wan Nur Zahidah Wan Zainon; Saniah Kormin; Nurasmaliza Mohd. Akhir; Muhammad Shah Ali (Chemical Engineering Diponegoro University, 2015)
Watermelon rind (Citrullus lanatus) dehydrated candy was prepared by using osmotic dehydration process that involves slow impregnation of syrup before drying at 50°C for 8, 14 and 20 hours. From the study, it can be seen that drying time significantly affected the moisture content of the watermelon rind dehydrated candy. The moisture content was significantly decreased with drying time. For colour evaluation, the L* value of watermelon rind dehydrated candy was slightly decreased with drying time while the a* value was slightly increased. Watermelon rind dehydrated candy that dried for 14 hours was the most preferred sample by the panelists as it received the highest score for texture, taste and overall acceptability attributes. So, it can be concluded that 14 hours of drying time is the most appropriate time to dry the candied watermelon rind.